2021
DOI: 10.1038/s41467-021-21656-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineered yeast genomes accurately assembled from pure and mixed samples

Abstract: Yeast whole genome sequencing (WGS) lacks end-to-end workflows that identify genetic engineering. Here we present Prymetime, a tool that assembles yeast plasmids and chromosomes and annotates genetic engineering sequences. It is a hybrid workflow—it uses short and long reads as inputs to perform separate linear and circular assembly steps. This structure is necessary to accurately resolve genetic engineering sequences in plasmids and the genome. We show this by assembling diverse engineered yeasts, in some cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 125 publications
0
27
0
Order By: Relevance
“…These isolates have previously been sequenced [22]. We resequenced these isolates using the Prymetime (v0.2) pipeline which uses both long reads and short reads to obtain a more contiguous genome assembly [61]. Using ERGO's Genome Align tool, we confirmed that there is a 12.8 kb region absent in B11220 but present in B11221.…”
Section: A 128 Kb Deletion Region Encodes Genes Involved In Alternate...mentioning
confidence: 84%
See 1 more Smart Citation
“…These isolates have previously been sequenced [22]. We resequenced these isolates using the Prymetime (v0.2) pipeline which uses both long reads and short reads to obtain a more contiguous genome assembly [61]. Using ERGO's Genome Align tool, we confirmed that there is a 12.8 kb region absent in B11220 but present in B11221.…”
Section: A 128 Kb Deletion Region Encodes Genes Involved In Alternate...mentioning
confidence: 84%
“…Reads were demultiplexed using the native software on the iSeq 100 machine. The C. auris B11220 and B11221 sequences were assembled using the Prymetime (v0.2) pipeline [61], which is a hybrid assembler using long and short reads.…”
Section: Genome Sequencing and Assemblymentioning
confidence: 99%
“…Moreover, the surface of the yeast colonies is smooth, sticky and easy to pick up and the texture of the colonies is uniform with the color of milky white, black or red. [ 84 ]…”
Section: Biofermentation Technology For Synthesis Of Bc‐based Materialsmentioning
confidence: 99%
“…Moreover, the surface of the yeast colonies is smooth, sticky and easy to pick up and the texture of the colonies is uniform with the color of milky white, black or red. [84] As for the fermentation process of yeast, it decomposes macromolecular substances into small molecules that can be easily metabolic via the system of intracellular and extracellular enzymes. The cultures of the yeasts depend on the liquid medium composed of yeast extract, glucose, and tryptone in deionized water with the proper pH value and temperature of 4.5-5.0 and 20-30 °C.…”
Section: Fermentation Of Yeasts For Bc-based Carbon Materialsmentioning
confidence: 99%
“…3,8−10 In this scenario, detecting genetic variations in biological replicates is important to establish a better knowledge about the association of genes and phenotypes. 3,6,11,12 The budding yeast Saccharomyces cerevisiae is a common chassis broadly used in metabolic engineering and synthetic biology studies. 13 Engineering in S. cerevisiae benefits from its well-studied genetics and well-developed genetic engineering tools.…”
Section: ■ Introductionmentioning
confidence: 99%